Linking Earth Observations for Assessing the Food Security Situation in Vietnam: A Landscape Approach - Poortinga, Ate; Nguyen, Quyen; Tenneson, Karis; Troy, Austin; Saah, David; Bhandari, Biplov; Ellenburg, Walter L.; Aekakkararungroj, Aekkapol; Ha, Lan; Pham, Hai; Nguyen, Giang; Chishtie, Farrukh (Frontiers in Environmental Science, 2019)
Land cover change and its impact on food security is a topic that has major implications for development in population-dense Southeast Asia. The main drivers of forest loss include the expansion of agriculture and plantation estates, growth of urban centers, extraction of natural resources, and water infrastructure development. The design and implementation of appropriate land use policies requires accurate and timely information on land cover dynamics to account for potential political, economical, and agricultural consequences. Therefore, SERVIR-Mekong led the collaborative development of a Regional Land Cover Monitoring System (RLCMS) with key regional stakeholders across the greater Mekong region. Through this effort, a modular system was used to create yearly land cover maps for the period 1988 - 2017. In this study, we compared this 30-year land cover time-series with Viet Nam national forest resources and agricultural productivity statistics. We used remote sensing-derived land cover products to quantify landscape changes and linked those with food availability, one of food security dimension, from a landscape approach perspective. We found that agricultural production has soared while the coverage of agricultural areas has remained relatively stable. Land cover change dynamics coincide with important legislation regarding environmental management and sustainable development strategies in Viet Nam. Our findings indicate that Vietnam has made major steps towards improving its' food security. We demonstrate that RLCMS is a valuable tool for evaluating the relationship between policies and their impacts on food security, ecosystem services and natural capital.